Temu Kembali Citra Berbasis Konten Pada Citra Lintas Domain - Yaya Wihardi; Herbert Siregar; Ali Mulyawan (STMIK Mardira Indonesia, Bandung, 2018)
This research aimed to develop a cross domain content based image retrieval system by using Histogram of Oriented Gradient (HoG) features. To compute visual similarity, we use Gaussian Approximation for Fast Image Similarity (GAFIS), Online Algorithm for Scalable Image Similarity Learning (OASIS), and Hybrid method that combine both of GAFIS and OASIS. The results show that the hybrid method outperforms the others, it is because the methods could extract uniqueness of each image query and image database by utilizing Gaussian parameters from negative-set and combine it with OASIS parameters Keywords : Image Retrieval, CBIR, Gaussian Approximation, OASIS.